The history of human space flight - Spitzmiller, Ted (University Press of Florida, 2017)
"A very competent, complete history of manned spacecraft. ... A strongly recommended resource."--Choice""A fascinating human saga of dedication, competition, sacrifice, and achievement.""--Dave Finley, National Radio Astronomy Observatory""An ambitious and thorough history, extending back to the earliest risk takers and innovators who laid the groundwork for the astronauts and cosmonauts who would break the bonds of Earth.""--George Leopold, author of Calculated Risk""Brings many of the personalities in the exploration of space to life. Spitzmiller offers a great perspective on issues from Vo.